Impact of Anxiety, Social Support, and Taegyo Practice on Maternal-Fetal Attachment in Pregnant Women Having an Abortion - BuKyung Kim; Mi Hae Sung (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of the study was to identify effects of anxiety, social support, and Taegyo practice toward maternal-fetal attachment in pregnant women having an abortion. METHOD: Participants included 99 pregnant women having an abortion, who participated in this study. Collected data were analyzed using descriptive statistics, t-test, ANOVA, Pearson's correlation, and multiple regression with the SPSS WIN 23.0 program. RESULTS: Maternal-fetal attachment was significantly negatively correlated with anxiety, and significantly positively correlated with social support and Taegyo practice. Spousal support and Taegyo practice, explained 43.8% of participants' maternal-fetal attachment. CONCLUSION: Results indicate that less anxiety and more social support, and Taegyo practice in pregnant women having an abortion, were associated with stronger maternal-fetal attachment. To strengthen the maternal-fetal attachment of pregnant women having an abortion experience, it would be necessary to develop and implement the Taegyo program, focusing on practicing Taegyo-related encouragement. Additionally, it is recommended that nursing intervention is provided, to encourage families to participate in the Taegyo practice together throughout the gestational period, and to maintain a positive relationship among partners.